A Convenient Formal [4+2] Heterocylization Route to Bis(triflyl)tetrahydroquinolines. Issue 54 (10th August 2021) - Lázaro‐Milla, Carlos; Almendros, Pedro
Abstract: We report the sustainable and efficient synthesis of a new type of quinoline derivatives bearing one or two SO2 CF3 groups. The protocol is metal‐, catalyst‐ and irradiation‐free, involves the use of readily available and stable precursors, and avoids the formation of side products. Also, the mild conditions of the process allow the tolerance of a wide range of functional groups. Abstract : Keep it simple : A sustainable approach (ethyl acetate under ambient conditions without metals, additives or irradiation) for the synthesis of di‐ and tetra‐hydroquinolines bearing one or two SO2 CF3 groups has been developed.A Convenient Formal [4+2] Heterocylization Route to Bis(triflyl)tetrahydroquinolines (Lázaro‐Milla and Almendros) @IQOG_CSIC